Transformasi Makna dan Fungsi Ruang di RPTRA Kalijodo dalam Pergulatan Citra Kota Jakarta - Permanasari, Eka; Lientino, Thomas (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2018)
Kalijodo has a long history in terms of gambling, prostitution, human trafficking and other illicit activities. Although it is a green belt area, the location had always being filled with semipermanent buildings. The area was changed its meaning in 2016 when the late Governor of Ahok with the help of the police and army, eradicated these housing and transformed this place as the community center (RPTRA-Ruang Publik Terpadu Ramah Anak). Together with Yori Antar, Basuki changed Kalijodo into a new center for Jakarta with its mural and skatepark. Former illicit users have been pushed out from the site. Some built a temporary shelter under the highway bridge while others went to their villages. After the fall of Basuki due to the blasphemy crime, the image of RPTRA Kalijodo was contested. Within a day, the area was filled with illegal parking and prostitution returned in different forms taking place under the highway bridge. Layers of meaning and use of Kalijodo transforms rapidly and in results changes the image of the city. Through observation, interviews and archival research, this paper analyses the contestation of the city image by investigating the relationship between the top-down approach and the everyday life uses of space.